The works of Bishop Butler - Butler, Joseph, 1692-1752 (Rochester studies in philosophy., 2006)
This edition of Bishop Joseph Butler's [1692-1752] complete works is the first newly edited version to appear in a century, and is the only one to include a single, analytic index to the whole works. The editor's introduction presents Butler's ethics and philosophy of religion as a single, comprehensive system of pastoral philosophy and surveys the vast influence Butler exerted, especially in the nineteenth century. Included here are all fifteen published sermons from Butler's tenure as Preacher at the Rolls Chapel, the only sermons in English routinely studied by secular ethicists to this day; six additional sermons on the great public institutions; his Charge to the Clergy at Durham, controversial in its day for its defense of external religion; his youthful letters sent anonymously to Samuel Clarke, and the complete text of his Analogy of Religion, an apologetic tour de force, including the famous introduction on probability as the guide to life, the analogical defense of immortality, free will and the moral order of nature, as well as his famous rebuttal of deism and his dissertations on virtue and on personal identify. Butler's work is among the monuments of classical Anglican theology. He is a major source for work in ethical theory and philosophy of religion, as well as for the background of Victorian literature. David E. White teaches philosophy at St. John Fisher College and is an officer in the New York State Philosophical Association.